From One Project to Another: Unintended Consequences and People’s Expectation of Climate Mitigation Project in Central Kalimantan - Manggala Ismanto (Jurnal Humaniora, 2022)
This paper discusses the dynamics of environmental interventions supported by aid projects and community responses as the subject of intervention. Drawing on ethnographic fieldwork, I looked into how connections between local and global entities occurred, between the local villagers in Central Kalimantan and the climate mitigation project of REDD +. Both of these entities met when the global discourse on climate change started to gain ground. This paper discusses how environmental interventions lead to different expectations and unintended consequences. I see community responses as choices and decisions which were historically constructed. These choices, expectations, and decisions are related to people’s experience with previous intervention agents and local livelihood dynamics. This local-global interaction has yielded unintended outcomes and led to different expectations for a REDD+’s demonstration activities project. When these two entities - local people and KFCP (Kalimantan Forest Climate Partnership) - meet in the global agenda to mitigate climate change, friction emerges due to a variety of interests in the village. My findings demonstrate how a reforestation program could lead to a socio-economic inequality. Land conflicts are likely to occur because of alternative livelihood programs which introduced rubber seeds.